APPLICATION OF SOLAR CELL TECHNOLOGY AS A SOURCE OF ENERGY LIGHTING TOOLS FOR CATCHING FISH IN STOOD CAGES - Sunarsono, Hery; Rahman, Taufiq; Mardiansyah, Yopy; Handayani, Vitri Aprilla (SIGMA TEKNIKA, 2023)
The method of catching fish carried out by traditional fishermen in "fisherman-cage" still uses petromax lamps with kerosene or lamps from generators that run on diesel fuel. These situations could cause oil spills that pollute the environment and are prone to fires. This community service program introduces a new energy source, by designing a solar-based lighting system (PLTS), where sunlight is converted into electric current and stored in batteries as a backup current at night. In this design, fishermen can optimize lighting by adjusting the position of the lamp according to the sea level at high and low tide to attract plankton and fish to enter the cage net. The design of the prototype has been tested in the TI-MR ITEBA laboratory with very satisfactory results, and then it was continued with serial production of 10 sets to be handed over to the fishing community. The fisherman directly recognized the success of the 10 sets of PLTS in increasing fish catches and getting environmentally friendly when the team visited the cage location